2017
DOI: 10.1021/acs.jced.7b00170
|View full text |Cite
|
Sign up to set email alerts
|

In Pursuit of a High-Temperature, High-Pressure, High-Viscosity Standard: The Case of Tris(2-ethylhexyl) Trimellitate

Abstract: This paper presents a reference correlation for the viscosity of tris­(2-ethylhexyl) trimellitate designed to serve in industrial applications for the calibration of viscometers at elevated temperatures and pressures such as those encountered in the exploration of oil reservoirs and in lubrication. Tris­(2-ethylhexyl) trimellitate has been examined with respect to the criteria necessary for an industrial standard reference material such as toxicity, thermal stability, and variability among manufactured lots. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
5
26
0
Order By: Relevance
“…and is described in several previous publications. In particular, the method has been applied by our group to correlate the high-pressure viscosity results for a large number of fluids of diverse types, from alkanes to aromatic hydrocarbons, , halocarbon refrigerants, , adipates, ,, and others. ,,, Recently, the application of this method has been extended with success to correlate the high-pressure viscosity results for an ionic liquid, namely, [EMIM]­[OTf] . According to this model, a reduced, dimensionless viscosity, η*, is defined as where M is the molar mass, R is the gas constant, T is the temperature, and V m is the molar volume, all properties in SI units.…”
Section: Resultsmentioning
confidence: 99%
“…and is described in several previous publications. In particular, the method has been applied by our group to correlate the high-pressure viscosity results for a large number of fluids of diverse types, from alkanes to aromatic hydrocarbons, , halocarbon refrigerants, , adipates, ,, and others. ,,, Recently, the application of this method has been extended with success to correlate the high-pressure viscosity results for an ionic liquid, namely, [EMIM]­[OTf] . According to this model, a reduced, dimensionless viscosity, η*, is defined as where M is the molar mass, R is the gas constant, T is the temperature, and V m is the molar volume, all properties in SI units.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, a new reference correlation for the viscosity of Tris(2-ethylhexyl) trimellitate (TOTM), was proposed. 103 The new correlation was designed to serve in industrial applications for the calibration of viscometers at elevated temperatures and pressures such as those encountered in the exploration of oil reservoirs and in lubrication. The correlation covers temperatures from (303 to 477) K, pressures from (0.1 to 200) MPa and viscosities from (1.6 to 760) mPa s. The uncertainty in the data provided is of the order of 3.2 % at a 95 % confidence level which was proposed by IATP as adequate for most industrial applications.…”
Section: Restricted Reference Correlationsmentioning
confidence: 99%
“…Several studies have reported structures of degradative products of diesters, whereas the structural details of polymerized products resulting from oxidation, as well as the polymerization mechanism, remain unclear . Despite the wide range of applications of trimellitate esters (eg, compressor oils, gear oils, and greases), there are few reports concerning their oxidation behavior . Therefore, in‐depth investigation of the oxidation mechanisms of DOA and TDTM base oils could provide a better understanding of their behavior and expand the range of suitable applications.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Despite the wide range of applications of trimellitate esters (eg, compressor oils, gear oils, and greases), there are few reports concerning their oxidation behavior. 19,20 Therefore, in-depth investigation of the oxidation mechanisms of DOA and TDTM base oils could provide a better understanding of their behavior and expand the range of suitable applications.…”
Section: Introductionmentioning
confidence: 99%